EKSEKUSI JAMINAN OBJEK FIDUSIA PASCA KELUARNYA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 71/PUU-XIX/2021 - Intan Permatasari, Amanda Devi; Hasbullah, Muhammad Afif; Serbabagus, Shalahudin (LAW Specialist Jurnal Ilmiah Hukum, 2024)
Law number 42 of 1999 concerning fiduciary guarantees regulates all matters regarding fiduciary guarantees, including the implementation of their execution, but in practice there are many discrepancies between the laws and regulations and the behavior of creditors towards debtors which are often arbitrary in withdrawing the object of guarantee. The Constitutional Court Decision No. 71/PUU-XIX/2021 aims to affirm and provide legal protection for the parties, before the existence of this Constitutional Court decision, creditors often used their right to execute directly without the need to go through the court, as long as it was carried out in accordance with the provisions of the applicable law. This is done by creditors to speed up the execution process and reduce the administrative burden experienced by the parties. However, the ruling also provides strict restrictions to protect the rights of debtors, including the obligation of creditors to provide clear and adequate notice before executing executions. In this study, the author uses a normative juridical research method or can be called a literature review and reviews legal materials, the approach taken by the author is the legal approach and also the case approach Where the case approach is carried out by reviewing or reviewing the results of the Constitutional Court decision number 71/PUU-XIX/2021. The analysis of legal materials is carried out by citing and studying relevant articles of laws and regulations, while the opinions of scholars are quoted and then used as a theoretical basis to answer research questions. From the explanation above, it can be concluded that this Constitutional Court decision can provide legal certainty and also provide legal protection for the parties because the results of this Constitutional Court decision require creditors to carry out the execution through an application to the district court.